1995
DOI: 10.1111/j.1651-2227.1995.tb13637.x
|View full text |Cite
|
Sign up to set email alerts
|

Total body irradiation: a neuropsychological risk factor in pediatric bone marrow transplant recipients

Abstract: Bone marrow transplantation (BMT) involves conditioning with cyclophosphamide and, for leukemic patients, total body irradiation (TBI). Based on the concern that this may lead to later neuropsychologic impairment in children, a longitudinal study was conducted. Thirty pediatric bone marrow transplant recipients, treated for leukemia or severe aplastic anemia (SAA), and their sibling donors, were given a neuropsychological examination in 1986 and 1988. A third follow-up study of patients treated before 12 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 19 publications
(26 reference statements)
0
28
1
Order By: Relevance
“…23 Our study was limited due to the small number of very young children it includes, and it failed to corroborate the existence of a significant relationship between low QoL and low age at SCT. On the other hand, when we look at the five individuals with moderately severe cognitive impairment, they do form a group that had lower QoL scores, particularly on the psychosocial subscales.…”
Section: Discussionmentioning
confidence: 83%
“…23 Our study was limited due to the small number of very young children it includes, and it failed to corroborate the existence of a significant relationship between low QoL and low age at SCT. On the other hand, when we look at the five individuals with moderately severe cognitive impairment, they do form a group that had lower QoL scores, particularly on the psychosocial subscales.…”
Section: Discussionmentioning
confidence: 83%
“…Intrathecal methotrexate, given alone or in combination with radiotherapy, has been closely associated with cerebral leukoencephalopathy, 23 especially in the pediatric population. 24 However, such risk is limited to 5% if systemic methotrexate is not administered. 25 Although spinal myelopathy has been observed following intrathecal methotrexate and/or cytarabine with craniospinal irradiation in children, 26 this experience is very limited and no formal association has been rigorously established.…”
Section: Discussionmentioning
confidence: 99%
“…The effective testing time was 4-5 h per child, allocated over 1 or 2 days, according to the needs of the individual child and family. The neuropsychological examination followed essentially the same protocol as our previous follow-up study, 13,14 covering the functional domains and tests presented in Table 2. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Tests of sensory-motor and specific cognitive functions, such as executive functions and memory, were included to the extent that the developmental level of the individual child permitted; in general, a complete neuropsychological examination could be performed in children who were 6.5 years or older at the time of assessment.…”
Section: Methodsmentioning
confidence: 99%
“…12 Our own longitudinal study of children treated at Karolinska University Hospital Huddinge during the 1980s presented an early account of the risks associated with pretransplant conditioning involving a 2-day CY regimen and subsequent TBI of 10 Gy in a single dose. 13,14 The results indicated that TBI in one dose was associated with sensory-motor and cognitive deficits and other neurological sequelae. These typically became more pronounced over time (45 year post-therapy), and were inversely related to age at treatment.…”
Section: Introductionmentioning
confidence: 97%